The Association of Crista Volume With Sesamoid Position as Measured From 3D Reconstructions of Weightbearing CT Scans. (May 2022) - Clarke, Audrey J.; Conti, Stephen F.; Conti, Matthew; Fadle, Amr A.; Ellis, Scott J.; Miller, Mark Carl
Background: Malposition of the sesamoids relative to the first metatarsal head may relate to intersesamoid crista underdevelopment or erosion. Using 3-dimensional models created from weightbearing CT (WBCT) scans, the current work examined crista volume and its relationship to first metatarsal pronation and sesamoid station. Methods: Thirty-eight hallux valgus (HV) patients and 10 normal subjects underwent weightbearing or simulated WBCT imaging. The crista was outlined by the inferior articular surface, and a line was drawn to connect the lowest point of each sulcus on either side of the intersesamoidal crista throughout the length of the crista. The volume was calculated. Sesamoid station and first metatarsal pronation were calculated from the 3D reconstructions. The mean crista volumes between HV and normal patients were statistically compared, as were the crista volume and pronation angle between sesamoid stations. Results: The mean crista volume in HV patients was 80.10 ± 35 mm 3 and in normal subjects was 150.64 ± 24 mm 3, which differed significantly between the 2 groups ( P < .001). Mean crista volumes were found to be statistically significantly different between the sesamoid stations ( P < .001) with decreasing crista volumes significantly and strongly correlated with increasing sesamoid station ( r = −0.80, P < .001). There was no difference in the mean pronation angle between the 4 sesamoid stations ( P = .37). The pronation angle was not associated with crista volume ( P = .52). Conclusion: HV patients have lower mean crista volume than normal patients. Crista volume is correlated with sesamoid station. Pronation of the first metatarsal was not associated with crista volume. Clinical Relevance: Crista volume may offer an additional determinant for the severity of hallux valgus.